Treatment of common ocular allergic disorders; a comparison of lodoxamide and NAAGA. Issue 10 (1st October 1998) - Denis, D; Bloch-Michel, E; Verin, P; Sebastiani, A; Tazartes, M; Helleboid, L; Di Giovanni, A; Lecorvec, M
Abstract : BACKGROUND/AIMS: Lodoxamide tromethamine and N -acetyl-aspartyl glutamic acid (NAAGA) are mast cell stabilisers, both of which have been shown to be effective in the treatment of allergic conjunctivitis. The aim of this study was to compare the two compounds in patients with common ocular allergic disorders. METHODS: 73 patients participated in a double masked, randomised multicentre study. Diagnoses were chronic allergic conjunctivitis, vernal conjunctivitis, seasonal and atopic conjunctivitis. 36 patients were treated with lodoxamide 0.1% and 37 with NAAGA 4.9%, the drops being instilled four times daily for up to 56 days. RESULTS: The overall opinion of the physicians and the patients was in favour of lodoxamide at day 10 of the study. At this time, 86% of lodoxamide treated and 49% of NAAGA treated patients considered they had improved. The patients' opinion favoured lodoxamide at day 28 and both physicians' and patients' evaluations were in favour of lodoxamide at day 42. Evaluation of signs and symptoms indicated superiority of lodoxamide at days 42 and 56. Both treatments were well tolerated. CONCLUSION: While both lodoxamide and NAAGA treatments are associated with clinical improvements in patients with allergic conjunctivitis, lodoxamide may have an earlier onset of action.